Legal Protection for Women Victims of Domestic Violence Due to Social-Media - Derry Angling Kesuma (Universitas Dharma Wacana, 2022)
The social media platform has assumed its role as a driver of innovation and revitalization. In addition to the role it plays in the transformation of information, social media also plays an important strategic role because it can serve as a means of communication between individuals and communities. However, the expansion of information and communication technology has also resulted in a negative impact, which can be seen in the rise of social media. The occurrence of domestic violence is one type of effect that has a negative effect (KDRT). The husband's jealousy if his wife uses social media against the opposite sex is one example of a form of domestic violence that social media can cause. Other examples include accessing social media accounts with the intent of stalking or spying on his wife, intimidating her, and other similar behaviors. Currently, the form of legal protection for women who commit acts of domestic violence is governed by the Criminal Code (KUHP), beginning with Article 351 and ending with Article 356; Article 6, Article 16 concerning protection; and Article 44 concerning criminal sanctions in Law No. 23 of 2004 regarding the Elimination of Domestic Violence. Law No. 23 of 2004 concerning the Elimination of Domestic Violence contains these provisions. The parameters for eliminating domestic violence are based on the law's adherence to four guiding principles: a) respect for human rights, b) gender justice and equality, c) non-discrimination, and d) victim protection. In the interim, these laws outline the forms of legal protection available to women who have been victims of domestic violence: (1) provision of temporary protection; (2) determination of the protection order by the court; (3) provision of a Special Service Room (RPK) at the police office; (4) provision of safe houses or alternative residences; and (5) provision of legal consultation by advocates for victims at the investigative level.